32.4k views
5 votes
A+c=r-d covert the equation to solve for a plz answer asap!!!!

User Zozo
by
5.1k points

2 Answers

5 votes

Answer:


\longmapsto \: a + c = r - d \\ (a + c) - c = (r - d) - c \\ \boxed{a = r - d - c}✓

  • a = (r - d - c) is the right answer.
User Samuel Hulla
by
5.8k points
5 votes

Answer:


a= r- d - c

Explanation:

Converting the equation to solve for a really just means getting a alone on one side of the equation.


a + c = r - d

To get a alone on the left, we can subtract c from both sides:


a+ c = r -d\\a = r - d - c (Since c - c = 0, c will disappear from the left side.)

Answer:
a= r- d - c

User Swastik Padhi
by
5.5k points